2018
DOI: 10.1016/j.biomaterials.2018.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Settable polymer/ceramic composite bone grafts stabilize weight-bearing tibial plateau slot defects and integrate with host bone in an ovine model

Abstract: Bone fractures at weight-bearing sites are challenging to treat due to the difficulty in maintaining articular congruency. An ideal biomaterial for fracture repair near articulating joints sets rapidly after implantation, stabilizes the fracture with minimal rigid implants, stimulates new bone formation, and remodels at a rate that maintains osseous integrity. Consequently, the design of biomaterials that mechanically stabilize fractures while remodeling to form new bone is an unmet challenge in bone tissue en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 74 publications
2
23
0
Order By: Relevance
“…Certain strategies appear more promising: For example, scaffolds seeded with MSCs that secrete B2BMP7, allowing for cells, the implanted scaffold, and secreted growth factors functioning synergistically in tissue regeneration [70]. Other promising strategies include those specifically targeted towards high-load bearing and rapid return to function [78]. Several innovative strategies have been used for achieving a well-defined pore structure, including NaCl particle leaching [57,58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain strategies appear more promising: For example, scaffolds seeded with MSCs that secrete B2BMP7, allowing for cells, the implanted scaffold, and secreted growth factors functioning synergistically in tissue regeneration [70]. Other promising strategies include those specifically targeted towards high-load bearing and rapid return to function [78]. Several innovative strategies have been used for achieving a well-defined pore structure, including NaCl particle leaching [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the degradation behavior has been identified as an important factor contributing to the rate of osteogenesis or new bone volume [18,81]. In a comparison of degradation kinetics under different loading conditions, it has been observed that mechanical loading may enhance the rate of degradation [78]. Results from studies reporting either enhanced osteogenesis (or greater bone formation) [32] or lack of a significant difference [34], in comparison to untreated or unfilled defects should be interpreted cautiously, since this tends to present a partially biased view of the biological/osteogenic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diflunisal was purchased from Sigma-Aldrich (St. Louis, MO) and dissolved in 100% DMSO at a final concentration of 10 mg/ml. Lysine triisocyanate (LTI) was purchased from Jinan Haohua Industry Co., Ltd. (Jinan, China) and refluxed with a dispersion of activated carbon (Fisher Scientific) in t-butyl methyl ether (TBME; Acros Organics) at 60°C for 22 h to remove high-molecular-weight impurities (43). For polyester triol synthesis, -caprolactone and stannous octoate were purchased from Sigma-Aldrich, and D,L -lactide and glycolide were purchased from Polysciences (Warrington, PA).…”
Section: Methodsmentioning
confidence: 99%
“…7 Stress shielding is characterized by an adaptation of the bone to the stress redistribution, 3,[8][9][10] resulting in the bone either becoming thinner or more porous. 11 In this context, biodegradable polymer composite materials containing bioactive glass have been proposed recently as an alternative to metal implants for clinical practice [12][13][14][15][16][17][18] where the glass filler improves the composite stiffness and bioactivity while the polymeric matrix provides toughness. In addition, these composite materials will prevent the patient from having a post-surgery to remove the prosthesis and will further allow a gradual load transfer from the prosthesis to the regenerating bone, thus eliminating the stress-shielding problem already mentioned.…”
Section: Introductionmentioning
confidence: 99%